Gold nanoclusters: Photophysical properties and photocatalytic applications - Cheng, Dajiao; Liu, Rong; Hu, Ke (Frontiers in Chemistry, 2022)
Atomically precise gold nanoclusters (Au NCs) have high specific surface area and abundant unsaturated active sites. Traditionally, Au NCs are employed as thermocatalysts for multielectron transfer redox catalysis. Meanwhile, Au NCs also exhibit discrete energy levels, tunable photophysical and electrochemical properties, including visible to near infrared absorption, microsecond long-lived excited-state lifetime, and redox chemistry. In recent years, Au NCs are increasingly employed as visible to near infrared photocatalysts for their high photocatalytic activity and unique selectivity. This review focuses on the photophysical properties of a variety of Au NCs and their employment as photocatalysts in photocatalytic reactions and related applications including solar energy conversion and photodynamic therapies.